Penggunaan Brand Ambassador Produk Scarlett Whittening Sebagai Strategi Komunikasi Pemasaran dalam Membangun Brand Image - Mulyani, Adinda Dwi; Suryasuciramdhan, Arfian; Sodikin, Sahrul; Suheti, Suheti; Rachmawati, Annisa Putri (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
This research concludes that brand ambassadors play a crucial role in marketing communications to build a strong brand image. The success of the brand ambassador strategy heavily relies on selecting the right individuals. The ideal brand ambassador should align with the characteristics of the brand being promoted, possess strong credibility in the public's eyes, have an appealing charm to consumers, and hold significant influence in shaping positive consumer perceptions. More than just the 'face' of the brand, brand ambassadors shape consumer perceptions of the marketed brand. The personality and image of the brand ambassador greatly influence how consumers perceive the brand's value, quality, and identity. Thus, this study emphasizes the close relationship between brand ambassadors and the brand image of a product. The selection of an appropriate and effective brand ambassador can significantly enhance the brand image desired by a company.To broaden understanding of this topic, further research is recommended to conduct comprehensive studies on the effectiveness of brand ambassadors across various industrial sectors. This aims to identify best practices and specific challenges within each industry. Additionally, understanding the diverse characteristics of consumers can help companies better tailor their brand ambassador strategies to different target markets. By applying these recommendations, future research can provide deeper insights into the role of brand ambassadors in shaping and strengthening brand image. Brand ambassadors play a vital role in marketing communication strategies as they can build and enhance the brand image of a product. Choosing the right brand ambassador, who aligns with the brand's character, credibility, appeal, and significant influence, can increase consumer trust, expand market reach, and drive purchase decisions.